Mastering wireless penetration testing for highly secured environments : scan, exploit, and crack wireless networks by using the most advanced techniques from security professionals - Johns, A. (Community experience distilled., 2015)
This book is intended for security professionals who want to enhance their wireless penetration testing skills and knowledge. Since this book covers advanced techniques, you will need some previous experience in computer security and networking.